\(\hept{\begin{cases}x\left(2\sqrt{y-1}-x\right)+y\left(2\sqrt{x-1}-y\right)=0\\x^3+y^3=16\end{cases}}\)
giai he pt
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Áp dụng BĐT AM-GM ta có:
\(\left(a+b+c\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\ge3.\sqrt[3]{abc}.3\sqrt[3]{\frac{1}{abc}}=9\)
Do \(a+b+c=1\)
nên \(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\ge9\)
Dấu "=" xảy ra khi \(a=b=c=\frac{1}{3}\)
Áp dụng BĐT AM-GM ta có:
\(\left(a+b+c\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\ge3.\sqrt[3]{abc}.3\sqrt[3]{\frac{1}{abc}}=9\)
Do \(a+b+c=1\)
nên \(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\ge9\)
Dấu "=" xảy ra khi \(a=b=c=\frac{1}{3}\)
Áp dụng BĐT AM-GM ta có:
\(\left(a+b+c\right)\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)\ge3.\sqrt[3]{abc}.3\sqrt[3]{\frac{1}{abc}}=9\)
Do \(a+b+c=1\)
nên \(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\ge9\)
Dấu "=" xảy ra khi \(a=b=c=\frac{1}{3}\)